Understanding Tea Consumer Loyalty in Banyumas: A SEM Analysis of Attitudes, Decisions, and Satisfaction - Muthia Auralia; Jangkung Handoyo Mulyo; Any Suryantini; Annisa Firdauzi; Pramesti Megayana (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
Indonesia, a major black tea, exported approximately 89% of black tea between 2018-2022, faces a substantial surplus, highlighting the need for producers to understand domestic consumer behavior amidst evolving tea consumption patterns. This study analyzes the influence of product attributes and the purchasing decisions of tea consumers in Central Java, Indonesia. This study employed a survey method. The study site was selected from the Banyumas District. Data were collected using purposive sampling techniques from 300 respondents and interviews with consumers who consumed black tea in tea bag packaging of original tea variants and/or jasmine tea, and made tea buying decisions. Data were analyzed using a combination of quantitative and structural equation modelling (SEM) with the analysis software AMOS 24. The results show that taste and brand have a significant effect on consumer attitudes; consumer attitudes have a significant effect on consumer purchasing decisions; consumer purchasing decisions have a significant effect on consumer satisfaction; and consumer satisfaction has a significant effect on consumer loyalty. The Ministry of Agriculture wants to reduce the export of raw materials and make the most of extra tea production. They plan to do so by promoting local tea brands. This will help Indonesian tea to become more known both internationally and locally. This will also improve the income of farmers and small businesses by increasing the value of their products.